Processes that drive the population structuring of Jenynsia lineata (Cyprinidontiformes, Anablepidae) in the La Plata Basin - Briñoccoli, Yanina F. (2021)
1. The distribution of genetic diversity across a species distribution range is rarely homogeneous, as the genetic structure among populations is related to the degree of isolation among them, such as isolation by distance, isolation by barrier, and isolation by environment. 2. Jenynsia lineata is a small viviparous fish that inhabits a wide range of habitats in South America. To decipher the isolation processes that drive population structuring in J. lineata, we analyzed 221 sequences of the mitochondrial cytochrome c oxidase I gene (COI), from 19 localities. Then, we examined the influence of the three most common types of isolation in order to explain the genetic variation found in this species. 3. Our results revealed a marked structuration, with three groups: (a) La Plata/ Desaguadero Rivers (sampling sites across Argentina, Uruguay, and Southern Brazil), (b) Central Argentina, and (c) Northern Argentina. A distance-based redundancy analysis, including the explanatory variables geographical distances, altitude, latitude, and basin, was able to explain up to 65% of the genetic structure. A variance partitioning analysis showed that the two most important variables underlying the structuration in J. lineata were altitude (isolation by environment) and type of basin (isolation by barrier). 4. Our results show that in this species, the processes of population diversification are complex and are not limited to a single mechanism. The processes that play a prominent role in this study could explain the high rate of diversity that characterizes freshwater fish species. And these processes in turn are the basis for possible speciation events.